2008
DOI: 10.1037/0021-9010.93.2.280
|View full text |Cite
|
Sign up to set email alerts
|

A review and meta-analysis of the nomological network of trainee reactions.

Abstract: A review and meta-analysis of studies assessing trainee reactions are presented. Results suggest reactions primarily capture characteristics of the training course, but trainee characteristics (e.g., anxiety and pretraining motivation) and organizational support also have a moderate effect on reactions. Instructional style (rho = .66) followed by human interaction (rho = .56) were the best predictors of reactions. Reactions predicted pre-to-post changes in motivation (beta = .51) and self-efficacy (beta = .24)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
227
0
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 222 publications
(242 citation statements)
references
References 133 publications
(73 reference statements)
6
227
0
9
Order By: Relevance
“…This is somewhat surprising considering the fact that trainee reactions have been the primary means by which organizations evaluate training programs (Sitzmann, 2008). Turning to cognitive learning, we found that 38 studies examined short-term effects of training, whereas only 9 studies looked at the long-term effects of training.…”
Section: Diversity Training Outcomesmentioning
confidence: 65%
“…This is somewhat surprising considering the fact that trainee reactions have been the primary means by which organizations evaluate training programs (Sitzmann, 2008). Turning to cognitive learning, we found that 38 studies examined short-term effects of training, whereas only 9 studies looked at the long-term effects of training.…”
Section: Diversity Training Outcomesmentioning
confidence: 65%
“…Training programs or learning initiatives that build efficacy and/or increase perceived control could have a positive impact on employee well-being. Researchers have indirectly addressed growth and well-being by studying the role of stress on learning and by examining learning outcomes such as self-efficacy, learners' reactions, and satisfaction (LePine et al 2004, Sitzmann et al 2008). There has, however, been limited examination of employee growth and well-being from a learning and development perspective.…”
Section: Well-beingmentioning
confidence: 99%
“…In both meta-analytic studies (Payne et al, 2007) and primary studies (DeRue & Wellman, 2009), task-specific self-efficacy is a proximal outcome of goal orientations, and research results demonstrate the importance of self-efficacy in improving learning outcomes (Schunk, 1991;Sitzmann, Brown, Casper, Zimmerman, & Polliard, 2008). Self-efficacy functions as the primary motivational mechanism by which goal orientation influences subsequent learning processes, where self-efficacy is defined as a belief in one' s ability to effectively perform and to exercise influence over events (Bandura, 1982).…”
Section: Current Research On Goal Orientationmentioning
confidence: 96%